Accelerometer-based analyses of animal sleep patterns - Yuuki Y Watanabe; Christian Rutz (eLife, 2022)
Body-motion sensors can be used to study non-invasively how animals sleep in the wild, opening up exciting opportunities for comparative analyses across species.